The art of problem posing - Brown, Stephen I. (Lawrence Erlbaum, 2005)
Describes and provides examples of the relationships between problem posing and problem solving, and explores the educational potential of integrating the two activities in classrooms. It encourages readers to shift their thinking about problem posing from the "other" to themselves and offers a broader conception of what can be done with problems.